Manajemen Produksi Film Pendek The Worthy Worship Tentang Sustainable Development Goals Menggunakan Teknik Stop Motion - Maharani Ayuning Tyas; Nawangsih Edynna Putri (LPPM Stikosa - AWS, 2024)
Film is a mass communication medium that can be used to convey messages in audio-visual form. Animation is a technique in film that combines moving images or objects that are made to appear moving. A combination of interesting stories, audio and visuals can support the success of conveying the message. The Worthy Worship is a short film that was awarded 2nd place in the LO Creative short video competition held by APTISI region VII East Java in 2022. The aim of this research is to find out how the production management of the short film The Worthy Worship uses Unique and creative integration of stop motion techniques and photography techniques. The process of making the short film The Worthy Worship goes through three stages, namely pre-production, production and post-production. The method used in this research is a case study with a qualitative descriptive research approach. Data collection uses observation, interview and documentation techniques. The results of this research show that the production management of the film The Worthy Worship went through three stages, namely pre-production, production and post-production. This research can be used as a reference in short film production management using technical skills in photography, videography and cinematography. The integration of stop motion techniques and photography can be used as an alternative in producing animated short films with simple equipment.